ISLAMIC BASED EDUCATION MANAGEMENT AND SOCIAL IN INDONESIA EDUCATIONAL INSTITUTIONS - Ramdanil Mubarok (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2022)
The problem of educational management that has not been maximized in Islamic and social content in an educational institution is a concern that needs to be solved so that the focus of the problem in this article is how to manage Islamic and social education in educational institutions? The aim is to analyze and interpret Islamic and socially charged educational management in educational institutions. This research is qualitative research with the type of library research (library research). The author collects various kinds of journal articles through Google Scholar, collects electronic books through Google Book and PDF Drive, then the author makes notes that are considered important and relevant according to the required data. The conclusion of this article is that Islamic-based education management in educational institutions is reflected in the implementation of deliberation in every decision that will be taken, knit together to produce maximum results in every job, and be productive in running the wheels of educational institutions. The management of social-based education in educational institutions should have life skills in social life such as individual/personal skills, social skills, academic skills, and skills in work. Thus, the management of socially charged education can be implemented in a flexible, participatory, comprehensive, and effective manner. It is hoped that writing this article, can contribute ideas that can strengthen the concept of educational management which contains Islamic values and social values in the management of educational institutions. Keywords: education management, Islamic content, social content.